The burden of an ageing society as a public debt - Helmut Siekmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2006)
Demographic change in industrialized nations has been a matter of common interest for some time. The financial implications of an ageing society are also increasingly discussed, particularly with regard to pension systems. The impact of this development on public finances is, however, only gradually being realized and the constitutional framework of public finances in Germany and the European Union just falls short of ignoring it entirely. This paper is a preliminary assessment of the burden of an ageing society under the fiscal law, specifically in respect of prospective entitlements to the public pension system. The first part analyses the provisions of the German constitution on finances (Finanzverfassungsrecht) to identify what rules, if any, exist addressing such (potential) expenditures, which lie in the immediate or very distant future. The second part of the paper analyses the fiscal requirements under European Union law. In the third and final part a few comments on the proposed national pact on stability and the recent moves to amend the German Federal Constitution are presented.
urn:nbn:de:hebis:30-70317
Keywords: 330